2020
DOI: 10.7150/thno.46142
|View full text |Cite
|
Sign up to set email alerts
|

A panel of eight microRNAs is a good predictive parameter for triple-negative breast cancer relapse

Abstract: Rationale: Triple-negative breast cancer (TNBC), which has the highest recurrence rate and shortest survival time of all breast cancers, is in urgent need of a risk assessment method to determine an accurate treatment course. Recently, miRNA expression patterns have been identified as potential biomarkers for diagnosis, prognosis, and personalized therapy. Here, we investigate a combination of candidate miRNAs as a clinically applicable signature that can precisely predict relapse in TNBC patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 71 publications
5
51
0
Order By: Relevance
“…Under pathological conditions, alterations in the miRNA expression levels are associated with a wide range of diseases, including cancer [ 82 , 83 , 84 ]. Furthermore, the in vitro and in vivo studies of disease-associated endogenous miRNAs have demonstrated their participation in the oncogenesis and tumor progression mechanisms in several cancers [ 85 , 86 , 87 , 88 ].…”
Section: Micrornasmentioning
confidence: 99%
“…Under pathological conditions, alterations in the miRNA expression levels are associated with a wide range of diseases, including cancer [ 82 , 83 , 84 ]. Furthermore, the in vitro and in vivo studies of disease-associated endogenous miRNAs have demonstrated their participation in the oncogenesis and tumor progression mechanisms in several cancers [ 85 , 86 , 87 , 88 ].…”
Section: Micrornasmentioning
confidence: 99%
“…It is reasonable to hypothesize that tumor evolution subsequent to tumor initiation is driven by selection of miRNA post-translational regulatory programs that favor proliferation, migration, invasion and metastasis. The prognostic implications of such tumor progression supporting programming is reflected in the discovery of a panel of miRNAs with prognostic predictive value in TNBC [ 103 ]. Specifically, the expression of eight miRNAs (miR-139-5p, miR-10b-5p, miR-486-5p, miR-455-3p, miR-107, miR-146b-5p, miR-324-5p and miR-20a-5p) was found to predict post-surgical relapse in TNBC patients.…”
Section: Mirnas In Triple-negative Breast Cancermentioning
confidence: 99%
“…Of all associated miRNAs, miR-139-5p showed the strongest correlation with disease free survival and TNM stage, although all associations with overall survival were weaker. Tumor suppressive function of miR-139 may involve regulation of targets including VEGFR, IGF-1R, HOXA10, Wnt, Ras, PI3K, NFκB and ROCK2 [ 103 , 104 ]. LOX, which is involved in collagen crosslinking, is targeted by miR-142.3p along with HIF1α and integrin subunit alpha 5 (ITGA5), thereby overcoming chemoresistance in TNBC [ 86 ].…”
Section: Mirnas In Triple-negative Breast Cancermentioning
confidence: 99%
“…Transcriptomic analysis provided the complex mRNAs and noncoding RNA expression patterns, which enables interpretation of the cell genomic codex. Applied to TNBC, it identifies deregulated miRNA expression patterns playing different roles as anti-oncomiR or oncomiR in tumor development, defining miRNA signatures related to prognosis [69,70] and stratification of TNBC into subclasses [71].…”
Section: Microrna Dysregulation On Tnbc With Basal-like Phenotype: Anmentioning
confidence: 99%